MEANING AND MYSTERY OF REALITY: My Search for Wisdom ‘In’ and ‘Beyond’ Reason - Vineeth, V F (Journal of Dharma, 2005)
vetaketu was young and energetic. He had just returned home after his training in the Vedas. Proud and puffed up, he developed a tendency to look down upon others and considered himself as educated with better reasoning, not subject to superstitions and idiosyncrasies. His father, Uddhalaka îruöi, a venerable master, very much admired by the seekers of sacred wisdom, noticed this unhealthy orientation in his son, called him to give him a lesson. He asked: “Do you know that ‘by which the unhearable becomes heard, unperceivable becomes perceived, the unknowable becomes known?’” (Chaöd. Up. VI.1.3). êvetaketu was totally surprised because he had no idea about it. Then, his father told him: “Just as, my dear, by one clod of clay all that is made of clay becomes known, the modification being only a name arising from speech, while the truth is that it is just clay” (Chaöd. Up. VI.1.4). What Uddhalaka îruöi was in mind was that whatever êvetaketu thinks to know is only the name and form of the One from whom everything has come. It was meant to be an eye opener to the student that the real wisdom begins only when we reach “That One” from whom everything proceeds, in whom everything rests, towards whom everything moves. The amazing student responded: “Verily, those venerable men did not know this; for if they had known it, why would they not have told it to me? Venerable sir, please tell me that.” “So be it, my dear,” said Uddhalaka Aruni.